2005
DOI: 10.1016/j.febslet.2005.11.068
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of MPP+ uptake by procyanidins in Caco‐2 cells: Involvement of oxidation/reduction reactions

Abstract: It is becoming increasingly evident that the absorption of certain nutrients and drugs and their effects are largely influenced by the concomitant ingestion of other substances. As various xeno-and endobiotics belong to the class of organic cations, the aim of this work was to study the modulation of the intestinal apical uptake of organic cations by diet procyanidins.Five procyanidin fractions with different structural complexity were obtained after fractionation of a grape seed extract. The effect of these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
19
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 25 publications
6
19
1
Order By: Relevance
“…Altogether, these results are compatible with a modulation of organic cation transport in Caco-2 cells through redox mechanisms, as has been previously advanced (Faria et al 2006).…”
Section: Discussionsupporting
confidence: 90%
“…Altogether, these results are compatible with a modulation of organic cation transport in Caco-2 cells through redox mechanisms, as has been previously advanced (Faria et al 2006).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study OPAs and PPAs exhibited strong effects on OVCAR-3 cell proliferation and apoptosis. Several studies have reported evidence that monomeric catechins and proanthocyanidin monomers, dimers and trimers can be absorbed through human intestinal Caco-2 epithelial cells (24,25). However, the results of the present study revealed that PPAs (prodelphinidin tetramers and higher polymerizations) exerted greater cytotoxic and apoptotic activities compared with OPAs (dimers and trimers) in general.…”
Section: Discussioncontrasting
confidence: 85%
“…However, studies by Holt et al (2002) demonstrated the presence of dimeric procyanidins in human plasma as early as 30 min after the consumption of a flavanol-rich food such as cocoa. There is evidence in support of absorption of monomeric catechins and proanthocyanidins through the human intestinal caco-2 epithelial cells (Deprez et al, 2001; Faria et al, 2006). Another study by Tsang et al (2005) reported the absorption and metabolism of catechin and proanthocyanidins up to trimers in urine following the oral intake of GSE.…”
Section: Introductionmentioning
confidence: 99%